2013
DOI: 10.1890/12-0406.1
|View full text |Cite
|
Sign up to set email alerts
|

Indirect effects on mutualisms: parasitism of bumble bees and pollination service to plants

Abstract: Researchers increasingly recognize the important role of mutualisms in structuring communities and view positive interactions in a community context rather than as simple pairwise interactions. Indirect effects, such as those that predators have on lower trophic levels, are a key process in community ecology. However, such top-down indirect effects have rarely been extended to mutualisms. Antagonists of one mutualist have the potential to negatively affect the second mutualist through negative effects on their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…Given that various pathogens have been observed to impair the foraging ability of bees (see discussion above), it would seem likely that pollination services are also altered or impaired. Gillespie & Adler [64], for example, found a negative correlation between Nosema infection rates in bumble bees at different field sites, and seed set of Trifolium and Solanum plants. Lach et al [10] found that honey bees infected with N. apis collected less pollen, and infection intensity was negatively correlated with the amount of pollen grains carried on the body of foragers, suggesting a lower efficiency of highly infected workers as pollinators.…”
Section: Are Diseases Reducing Pollination Services?mentioning
confidence: 99%
“…Given that various pathogens have been observed to impair the foraging ability of bees (see discussion above), it would seem likely that pollination services are also altered or impaired. Gillespie & Adler [64], for example, found a negative correlation between Nosema infection rates in bumble bees at different field sites, and seed set of Trifolium and Solanum plants. Lach et al [10] found that honey bees infected with N. apis collected less pollen, and infection intensity was negatively correlated with the amount of pollen grains carried on the body of foragers, suggesting a lower efficiency of highly infected workers as pollinators.…”
Section: Are Diseases Reducing Pollination Services?mentioning
confidence: 99%
“…Bumblebees offer us an excellent model system to study the indirect effects of parasitism on mutualisms [ 20 ]. The majority of Bombus spp., are generalist pollinators, foraging on many native wild and crop plants in diverse terrestrial habitats in temperate regions [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is likely (with increased sampling) that all other associated NPFW suffer fitness limitations due to infection, suggesting that nematode infection may remove a sizeable proportion of the total wasp-antagonist community in each generation. This may be explained as an indirect effect (Gillespie andAdler 2013, Guimarães et al 2017) or may represent a novel density-dependent facultative mutualism between Parasitodiplogaster nematodes, Pegoscapus pollinating wasps, and F. petiolaris. When more NPFWs exploit the mutualism they are more likely to encounter nematodes whose infection they are sensitive to, making them unlikely to arrive at a new fig and reproduce.…”
Section: Nematode Infection Effects On Npfw Life Historymentioning
confidence: 99%